Prolactin directly stimulated the solvent drag-induced calcium transport in the duodenum of female rats - Chaiyot Tanrattana (2018)
Prolactin has been reported to stimulate the calcium absorption of the duodenum where three components of the active calcium transport, namely transcellular active, voltage-dependent and solvent drag-induced calcium transport, were identified. It was known that the transcellular active, but not the voltage-dependent, duodenal calcium transport was directly stimulated by prolactin. The present study thus aimed to evaluate the direct action of prolactin on the solvent drag-induced duodenal calcium transport by using the Ussing chamber technique. The jejunum was used as a reference for the existence of solvent drag and the widening of tight junction induced by cytochalasin E. Results showed that the solvent drag-induced calcium transport existed in both intestinal segments, but the magnitude was significantly greater in the duodenum (29.27±2.27 vs. 17.31±1.65 nmol h-1cm-2, P<0.001). We further demonstrated that 200, 600 and 800, but not 1000 ng/ml, prolactin significantly promoted the solvent drag-induced duodenal calcium transport in a dose-response manner, i.e. from the control value of (nmol h-1cm-2) 24.31±2.36 to 45.42±3.47 (P<0.01), 63.82±5.28 (P<0.001) and 53.93±5.41 (P<0.01), respectively. However, prolactin did not manifest any effect on the jejunum. Because the paracellular transport was suggested to be size-selective as well as charge-selective, further experiments were designed to evaluate the mechanism by which prolactin stimulated the solvent drag-induced calcium transport. The duodenum was exposed to 20 μM cytochalasin E, 600 ng/ml prolactin or the combination of both in the presence of a paracellular marker3H-mannitol, while the jejunum was a positive reference. The results showed that, in the jejunum, cytochalasin E alone and cytochalasin E plus prolactin significantly increased the mannitol fluxes from (μmol h-1cm-2) 0.29±0.04 to 0.49±0.03 (P<0.05) and 0.48±0.05 (P<0.05), respectively, while having no effect on the calcium fluxes. Prolactin alone had no effect on the jejunal calcium flux. In the duodenum, neither mannitol nor calcium fluxes were enhanced by cytochalasin E, however, prolactin still increased the solvent drag-induced calcium flux from 27.74A±2.41 to 51.03±4.35 nmol h-1cm-2(P<0.001). It was concluded that prolactin directly stimulated the solvent drag-induced duodenal calcium transport in a dose-response and biphasic manner without the widening of tight junction. © 2004 Elsevier B.V. All rights reserved.